2006
DOI: 10.1099/mic.0.28347-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the Bradyrhizobium japonicum modA and modB genes involved in molybdenum transport

Abstract: A modABC gene cluster that encodes an ABC-type, high-affinity molybdate transporter from Bradyrhizobium japonicum has been isolated and characterized. B. japonicum modA and modB mutant strains were unable to grow aerobically or anaerobically with nitrate as nitrogen source or as respiratory substrate, respectively, and lacked nitrate reductase activity. The nitrogen-fixing ability of the mod mutants in symbiotic association with soybean plants grown in a Mo-deficient mineral solution was severely impaired. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 45 publications
2
37
0
5
Order By: Relevance
“…In the case of B. japonicum soybean bacteroids, transcriptomic analysis (Pessi et al 2007) revealed that components of the molybdenum uptake system ModABC were amongst the most strongly induced genes in bacteroids (over 120-fold as compared to free-living cells). This data is consistent with the relevant symbiotic role of this transporter deduced from the mutant analysis mentioned above (Delgado et al 2006). Further proteomic analyses of B. japonicum bacteroids induced in soybean indicate the presence of proteins involved in iron transport, including the TonB-dependent ferrichrome receptors blr3904 and bll4920 (Delmotte et al 2010).…”
Section: Global Analysis Of Expression Of Bacterial Metal Uptake Systemssupporting
confidence: 75%
See 1 more Smart Citation
“…In the case of B. japonicum soybean bacteroids, transcriptomic analysis (Pessi et al 2007) revealed that components of the molybdenum uptake system ModABC were amongst the most strongly induced genes in bacteroids (over 120-fold as compared to free-living cells). This data is consistent with the relevant symbiotic role of this transporter deduced from the mutant analysis mentioned above (Delgado et al 2006). Further proteomic analyses of B. japonicum bacteroids induced in soybean indicate the presence of proteins involved in iron transport, including the TonB-dependent ferrichrome receptors blr3904 and bll4920 (Delmotte et al 2010).…”
Section: Global Analysis Of Expression Of Bacterial Metal Uptake Systemssupporting
confidence: 75%
“…B. japonicum mutants affected in the mod system lack nitrate reductase activity in free living cultures, and show reduced levels of nitrogen fi xation in symbiosis with soybean. These defi ciencies were corrected by addition of molybdenum to the plants (Delgado et al 2006). Such complementation has a strong dependence on the presence of sulfate, suggesting that, in addition to being mainly incorporated through the Mod system, molybdate is also taken up through sulfate transporters under symbiotic conditions, as it has been shown for a plant sulfate transporter (Fitzpatrick et al 2008).…”
Section: Abc Transportersmentioning
confidence: 99%
“…Leptospirillum group III carries all the genes for nitrogen fixation (75,76). These are next to a cluster of molybdenum uptake genes necessary for nitrogen fixation (22). Notably, in our current analysis, the proteins involved in nitrogen fixation were not identified in any of the samples (see Table S2 in the supplemental material).…”
Section: Comparative Genomics (I) Energy Metabolism (A) Electron Trmentioning
confidence: 76%
“…ABC-T SMc03869 was induced by thiamine limitation (11-fold) and has 57% identity with the characterized thiamine transporter (Thi) from S. typhimurium (39). ABC-T SMc03196, induced 12-fold by molybdate limitation, has 58% identity with the characterized molybdate transporter (Mod) from B. japonicum (40). Finally, ABC-T SMc04245 induced 37-fold by zinc limitation has 33% identity with the characterized zinc transporter (Znu) from E. coli (41).…”
Section: Site the Results Are Shown In Full Inmentioning
confidence: 99%